Maatalouspolitiikan ja taloudellisten kannustimien vaikutus kasvintuotantotilojen pellon käyttöön - Niemi, Jarkko K. (MTT, 2001)
Voimakkaat muutokset viljojen hinta- ja tukisuhteissa voivat aiheuttaa tulovaikutusten lisäksi muutoksia maatilojen pellon käyttöön. 1980-luvulla aloitettujen ja EU-jäsenyyden myötä jatkuneiden maatalouspolitiikan uudistusten on arvioitu vähentäneen leipäviljojen viljelyä, sillä tukiratkaisujen ei ole katsottu kannustavan leipäviljojen viljelyyn. Käsillä olevassa tutkimuksessa on selvitetty ekonometristen mallien avulla, miten maatalouspolitiikka, viljanviljelyn taloudelliset kannustimet ja tilakoko ovat vaikuttaneet kasvintuotantoa harjoittavien kirjanpitotilojen pellon käyttöön. Tutkimustulosten mukaan kasvintuotantotilojen pellon käyttö sopeutuu erittäin joustavasti viljojen hintasuhteissa tapahtuviin muutoksiin. Vehnän ja rehuviljan hintasuhteilla on suuri merkitys etenkin vehnän viljelyyn. Tämän vuoksi maatalouspolitiikalla voidaankin vaikuttaa tehokkaasti leipäviljojen viljelyaloihin. Myös tilan koolla näyttää olevan vaikutuksia kasvintuotantoa harjoittavien tilojen pellon käyttöön. Viljantuotannossa saavutettavien mittakaavaetujen vuoksi kesannointihalukkuus vähenee ja leipäviljojen viljely lisääntyy, kun tilakoko kasvaa.

Supply for bread and feed grains is volatile in Finland. The large volatility is a result of annual variation in grain yields per hectare and grain areas. Farmers can respond to changing market and policy regimes by adjusting land allocations to different grains, because they are cultivated by the same machinery. Therefore, it is expected that the large changes in subsidy rates and prices have changed land areas allocated to bread and feed grains, which implies significant supply effects. This paper estimates an econometric model of land allocation on Finnish arable land farms in 1989- 1998. Allocation equations were estimated simultaneously by seemingly unrelated regression for feed grains, winter wheat, summer wheat, rye and voluntary set-aside. The results suggest that land allocation on Finnish arable farms responds elastically to the changes in grain prices. Especially wheat allocation is elastic with respect to its own price. Land allocations will respond also to the acreage subsidies. Particularly, wheat area was elastic with respect to subsidies paid for wheat area. The joint effects of compensating decreasing grain prices through acreage-based subsidies has increased the amount of land allocated to feed grains. Bread grain land and set-aside areas were elastic with respect to fertiliser price. An increase in fertiliser price shifts land from bread grains to set-aside. This is reasonable, as bread grain production is more fertiliser intensive than feed grain production and set-aside. An increase in farm size increased winter wheat and rye areas and decreased set-aside acreage. Thus, size economies make the set-aside programs less attractive and encourage allocating land on bread grains.
Julkaisussa virheellinen ISSN 1239-4548
Keywords: Ma; hinnat; tukimuodot; vehnä; ohra; ruis; kaura; pellon käyttö; ekonometria; kesanto; land allocation; econometrics; prices; subsidies; wheat; barley; rye; oats; set-aside